Perancangan Maskot Ngalup Coworking Space Malang - Iman Firmansyah; Rahmat Kurniawan; Zusana Eko Pudyastuti (MAVIS : Jurnal Desain Komunikasi Visual, 2022)
In an effort to support the effectiveness of sales, various production methods and processes as well as promotional activities in creating, introducing and selling the resulting products will be widely encountered in the current era. One of the means to sell products is to use print media and electronic media as promotional tools and means of communication. Utilization of print media, produces something in physical form, in addition to the use of electronic media, it produces some content to retain customers with social media features. This paper will discuss the process of designing a mascot as one of the promotional media to increase the selling value of a brand.